الدور الوسيط لصافي رأس المال العامل في العلاقة بين قوة السوق وإداء صناعة التأمين في فلسطين - أبو عواد، بهاء صبحي (جامعة فلسطين التقنية خضوري - عمادة البحث العلمي, 2022)
تهدف هذه الدراسة إلى اختبار نظريات قوة السوق ودورها في تفسير أداء صناعة التأمين في فلسطين بوجود الدور الوسيط لصافي رأس المال العامل بالاعتماد على البيانات المتوفرة ل (7) شركات خلال الفترة من (2010 - 2020)، وباستخدام النماذج القياسية استطاعت نظريات قوة السوق تفسير عوائد قطاع التأمين الفلسطيني. وعليه؛ فإن هذه النتائج تنفي وجود تأثير للاحتكار في هيكلية قطاع التأمين على أداء هذه الشركات، وكذلك وجود تأثير للكفاءة التقليدية على أدائها. فقطاع التأمين في فلسطين يتميز بالتنافسية المقبولة وهذا ما يؤكده الدور المحوري لصافي رأس المال العامل في تعزيز عوائد تلك الشركات. وتوصي الدراسة بضرورة تركيز شركات التأمين على تعزيز قدراتها التشغيلية وتوجيه الحجم الأكبر لأصولها المتزايدة في دعم رأس المال العامل لما له من دور بارز في أداء هذه الصناعة. ويبقى البحث مستقبلا عن دور نظريات الكفاءة الاقتصادية في تفسير عوائد قطاع التأمين في فلسطين. This study aims to examine market power theories and their role in explaining the performance of the insurance industry in Palestine with the presence of the mediating role of net working capital. Based on the data available for (7) companies during the period (2010-2020), and using standard Models; Market power theories are able to explain the returns of the Palestinian insurance sector. Accordingly, these results deny the influence of monopoly in the structure of the insurance sector on the performance of these companies, and the impact of traditional efficiency on its performance. The insurance sector in Palestine is characterized by acceptable competitiveness, and this is confirmed by the pivotal role of net working capital in enhancing the returns of these companies. The study recommends the need for insurance companies to focus on enhancing their operational capabilities and directing the largest volume of their growing assets to support working capital. This leads to achieve prominent role in the performance of this industry. The future research remains on identifying the role of economic efficiency theories in explaining the returns of the insurance sector in Palestine.
Keywords: الإدارة المالية -- البنوك التجارية -- السوق المالي -- تقييم الأداء -- فلسطين